THE EFFECTIVENESS OF COMIC-BASED INSTRUCTIONAL MEDIA FOR TEACHING ARABIC AT MUHAMMADIYAH ELEMENTARY SCHOOL, WARAUNAN, SOLO - Hani'atul Mabruroh; Tina Ulwiana; Fajar Nur Syah Alam (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2024)
Arabic language education often faces both linguistic and non-linguistic challenges. This research is motivated by the fact that some students struggle to understand Arabic material because teachers teach without media and rely on outdated methods. The purpose of this study is to determine the effectiveness of picture media (comics) in improving the Arabic learning outcomes of fourth-grade students at Muhammadiyah Elementary School Solo. This is a quantitative experimental study, employing a pre-test and post-test design with a single group. Data collection was carried out through tests, and data analysis was conducted using a t-test. Since the data was not normally distributed but homogeneous, the researcher used the Wilcoxon test with the assistance of SPSS 25. The average post-test score was 77.00, while the pre-test score was 66.5. The Wilcoxon test result showed a sig (2-tailed) value of 0.006, which is less than 0.05. Therefore, it can be concluded that the use of picture media is proven to be effective.